A study of vaccine-induced immune pressure on breakthrough infections in the Phambili phase 2b HIV-1 vaccine efficacy trial. Issue 47 (11th November 2016) - Hertz, T.; Logan, M.G.; Rolland, M.; Magaret, C.A.; Rademeyer, C.; Fiore-Gartland, A.; Edlefsen, P.T.; DeCamp, A.; Ahmed, H.; Ngandu, N.; Larsen, B.B.; Frahm, N.; et al.
Abstract: Introduction: The Merck Adenovirus-5 Gag/Pol/Nef HIV-1 subtype-B vaccine evaluated in predominately subtype B epidemic regions (Step Study), while not preventing infection, exerted vaccine-induced immune pressure on HIV-1 breakthrough infections. Here we investigated if the same vaccine exerted immune pressure when tested in the Phambili Phase 2b study in a subtype C epidemic. Materials and methods: A sieve analysis, which compares breakthrough viruses from placebo and vaccine arms, was performed on 277 near full-length genomes generated from 23 vaccine and 20 placebo recipients. Vaccine coverage was estimated by computing the percentage of 9-mers that were exact matches to the vaccine insert. Results: There was significantly greater protein distances from the vaccine immunogen sequence in Gag (p = 0.045) and Nef (p = 0.021) in viruses infecting vaccine recipients compared to placebo recipients. Twenty-seven putative sites of vaccine-induced pressure were identified (p < 0.05) in Gag (n = 10), Pol (n = 7) and Nef (n = 10), although they did not remain significant after adjustment for multiple comparisons. We found the epitope sieve effect in Step was driven by HLA A∗02:01; an allele which was found in low frequency in Phambili participants compared to Step participants. Furthermore, the coverage of the vaccine against subtype C Phambili viruses was 31%, 46% and 14% for Gag, Pol and Nef, respectively, compared to subtype B Step virus coverage of 56%, 61% and 26%, respectively. Discussion: This study presents evidence of sieve effects in Gag and Nef; however could not confirm effects on specific amino acid sites. We propose that this weaker signal of vaccine immune pressure detected in the Phambili study compared to the Step study may have been influenced by differences in host genetics (HLA allele frequency) and reduced impact of vaccine-induced immune responses due to mismatch between the viral subtype in the vaccine and infecting subtypes.